Comparative Analysis of the Elongation Measurement Methods During Static Tension Testing of Metals - Hajdukiewicz, G. (Scientific Journal of Gdynia Maritime University, 2018)
In the article there are presented and compared elongation measurements of the metal specimens made of AlMg3 alloy. The specimens were obtained by 2 methods during performing the metal tension test at ambient temperature according to standard PN-EN ISO 6892-1:2010. The 1st method – elongation measurement with video extensometer VideoXtens-type of the Zwick&Roell company. The 2nd method – elongation measurement based on initial division of measurement length.